Pengaturan Kecepatan Spindle Mesin Bubut Retrofit Menggunakan VSD (Variable Speed Drive) - Ismail, Andhi Akhmad; Hendaryanto, I. Aris (Proklamasi 45 University, 2024)
Retrofitted milling machines are usually not equipped with a gear box to control spindle rotation, so they will experience difficulties if varied spindle shaft rotation is desired. The commonly used way to adjust the rotation of the spindle shaft so that it can vary is by adjusting the rotation of the spindle drive induction motor using a Variable Speed Drive (VSD). The research started by removing the old single phase induction motor and replacing it with a three phase induction motor, then creating a control circuit so that the VSD could work automatically with commands from the breakout board. The rotation adjustment is carried out using a potentiometer installed on the VSD. Spindle shaft rotation is detected using a pulse meter which gets a signal from an inductive proximity sensor and is installed on the spindle shaft. Experiments during the research showed that the spindle rotation could be adjusted using VSD properly, starting from a speed of 0 rpm to 2000 rpm. The spindle experiences a decrease in speed when subjected to a load, most likely due to slippage that occurs from the drive pulley which is rotated by the drive induction motor to the spindle pulley because it uses a belt transmission.